2005
DOI: 10.1161/circulationaha.105.541649
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Associated Risk Factors for Aortic Valve Replacement in 160 Children

Abstract: Background-We sought to define patient characteristics, outcomes, and associated risk factors after aortic valve replacement (AVR) in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 37 publications
4
93
1
1
Order By: Relevance
“…For example, the study of T. Karamlou et al showed that the complications in the postoperative period were diagnosed in only 10 of 53 patients, whereas in this study the overall complication rate reached 51.5% [8]; however, differences in the structure of the complications were minor. In a study by T. Karamlou et al and our study, pericarditis and cardiac arrhythmias were the leading complications, but T. Karamlou et al also noted a relatively high incidence of bleeding in the postoperative period, whereas in our study, the pericardial effusion and cardiac/respiratory failure were observed more frequently.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…For example, the study of T. Karamlou et al showed that the complications in the postoperative period were diagnosed in only 10 of 53 patients, whereas in this study the overall complication rate reached 51.5% [8]; however, differences in the structure of the complications were minor. In a study by T. Karamlou et al and our study, pericarditis and cardiac arrhythmias were the leading complications, but T. Karamlou et al also noted a relatively high incidence of bleeding in the postoperative period, whereas in our study, the pericardial effusion and cardiac/respiratory failure were observed more frequently.…”
Section: Discussioncontrasting
confidence: 64%
“…Comparison of the freedom from reoperations after the Ross procedure and other types of surgical interventions on the aortic valve revealed no significant difference. At the same time, according to other studies, in a 10-year followup reoperations were required in 26% of patients after aortic valve replacement and 28% of patients after an open commissurotomy [8,9]. When comparing the results of our study with the above-mentioned data, their longer duration of the follow-up must be taken into account; at the same time, the identified trends are very revealing because they were based on an analysis of a large single-center study.…”
Section: Discussionmentioning
confidence: 64%
“…Although mechanical valves are durable, they have many disadvantages including the necessity for life-long anticoagulation, risks of endocarditis, bleeding, and thromboembolic events. [6,7] Even reoperation is required in at least 10% of mechanical valves by 20 years for endocarditis, paravalvular leak, thrombotic, or hemorrhagic complications or pannus formation with obstruction. Mechanical valves are also more problematic in female patients in childbearing age who need aortic valve replacement, leading to severe social and psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical valves are also more problematic in female patients in childbearing age who need aortic valve replacement, leading to severe social and psychological distress. [6,7] Although bioprosthetic valves do not require anticoagulation, their long-time durability is not optimal in young patients. [4] The ideal valve substitute in children, therefore, should have somatic growth, no need for anticoagulation with excellent hemodynamic properties, resistance to infection, and long-term durability.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, its safety and reproducible implantation technique, good hemodynamic performance, low incidence of valve-related events, acceptable short and long-term outcomes and prolonged durability, convert it into a good alternative in cases where aortic valve replacement is mandatory (Alexiou et al, 2000). The longevity of mechanical prostheses is superior compared to bioprosthetic valves, but its implantation has been associated with very high early re-intervention rate and poor survival in neonates and small infants, limiting its use in these ages (Karamlou et al, 2005). Aortic valve replacement using mechanical prosthetic valves in children often requires annular enlargement to insert commercially available prostheses.…”
Section: Mechanical Valve Replacementmentioning
confidence: 99%